ANALYSIS AND DESIGN OF DIGITAL APPLICATION SYSTEMS FOR EMPLOYEE DATA MANAGEMENT IN XYZ STORE - Setiawan, Wawan; Fajriyah, Nurul (Universitas Muhammadiyah Tangerang, 2024)
As technology and information systems develop in the digital era, managing employee data has become very important for organizations and companies. An efficient and accurate employee data input process is the first step in managing human resources optimally. XYZ Shop is a shop located in the Banten area, which sells retail goods to end consumers, usually on a small scale and at home. The shop provides a variety of products, ranging from clothing, food, electronic goods, to household equipment. However, the XYZ store still faces challenges in managing employee data, such as limited time and human energy in carrying out this process because it is still manual. To overcome this problem, an employee data input program was designed to be an effective solution. With this program, the employee data management process can become more efficient, accurate and organized. The author used three techniques for data collection activities, namely observation, interviews and literature study. Development of an application program system for managing employee data at XYZ store using the PHP programming language and MySql database. The application system built is web-based, so it can be accessed easily anywhere and anytime. This provides immediate benefits in day-to-day operational efficiency, allowing human resources to focus on more strategic tasks. With the ability to manage employee data efficiently, stores can easily adapt to company growth, including branch expansion and increased employment